ANALISIS TUMBUH TANAMAN KENTANG ( Solanum tuberosum L) DI DATARAN MEDIUM DENGAN BEBERAPA JARAK TANAM - Patricia Kaseger; J. E. X. Rogi; Stella Tullung (COCOS, 2017)
ABSTRACTThis study aims to analyze the growth of potato plants in the medium plains anddetermine the best spacing for potato crops in the medium plains. This research wasconducted using Randomized Block Design, 3 treatments and 3 replications. Thisresearch was conducted from July to October 2016 in Walian Village, TomohonCity. The plant material used is potato plant varieties Granola. The treatments werePlant Spacing (90 cm × 30 cm), Plant Spacing (70 cm × 30 cm) and Plant Spacing(50 cm × 30 cm). Variable observations include: 1) liniear growth rate, 2) longgrowing period and 3) maximum dry weight of the potato plant. The data obtainedwere analyzed by using the Least Significance Difference (LSD) 5%. The resultsshowed that plant spacing treatment had an effect on linear growth rate andmaximum dry weight of plant crop. While the best spacing for potato plants is plantspacing of 90 cm × 30 cm.Keywords: the potatos, medium plains, plant spacing